2000
DOI: 10.1002/1097-4547(20000815)61:4<421::aid-jnr8>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative and migratory responses of astrocytes to in vitro injury

Abstract: An in vitro "scratch-wound" model was used to evoke and investigate some astroglial responses to mechanical injury. The changes in the morphology, locomotion, and proliferation of injured astrocytes were analysed under culture conditions devoid of blood-derived cells responsible for activating the inflammatory cascade. The rate of proliferation was determined by immunocytochemical detection of BrdU-incorporating cells located next to or far from the wound. The motility of individual cells and the mass-advancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 29 publications
2
48
0
2
Order By: Relevance
“…30 We suggest that these studies could be done more efficiently using electrode arrays, even without image reconstruction. Using an array of microelectrodes, the migration velocities can be studied over a longer period of time compared to singleelectrode techniques such as the ECIS technique, 31 since the sensing surface is larger.…”
Section: Discussionmentioning
confidence: 99%
“…30 We suggest that these studies could be done more efficiently using electrode arrays, even without image reconstruction. Using an array of microelectrodes, the migration velocities can be studied over a longer period of time compared to singleelectrode techniques such as the ECIS technique, 31 since the sensing surface is larger.…”
Section: Discussionmentioning
confidence: 99%
“…We also used a limited number of media components, and did not find it necessary to include progesterone (Jung et al 2002;Tanaka et al 1994;Tenenbaum et al 2004), medications including antibiotics and antimycotics (Cavaliere et al 2006;Jakovcevski and Zecevic 2005;Tanaka et al 1994), transferrin (Jung et al 2002;Tenenbaum et al 2004), sodium selenite (Tanaka et al 1994;Tenenbaum et al 2004), or sodium pyruvate (Tanaka et al 1994) to maintain tissue cytoarchitecture. Additionally, we used MEM because it is often used to maintain astrocyte cell cultures, and may thus promote preservation of astrocytes in our organotypic explants (Kornyei et al 2000).…”
Section: Applications Of Human Ex Vivo Models and Technique Modificatmentioning
confidence: 99%
“…The central scratch has been used with multiple cell types and, as the monolayers heal the wound in a characteristic manner, they have been used to study cell polarization, matrix remodeling, cell migration, and numerous other processes [12]. Kornyei et al (2000) [14] used an in vitro scratch-wound model to investigate astroglial responses to mechanical injury while Saga et al (2003) [15], Liang et al (2004) [16], Farooqui et al (2004) [17], and Walker et al (2004) [18] used the cell scratch-wound model to study the proliferative and migratory responses of different cells. Lau et al (2001) [19] focused on the production of four inflammatory cytokines in primary culture using an injury model which simulated in vivo mechanical trauma and reported that all four cytokines began to increase 1 hour post-scratch and remained at high levels throughout the experiment [19].…”
Section: Introductionmentioning
confidence: 99%